Ethics of mobile phone surveys to monitor non-communicable disease risk factors in low- and middle-income countries: A global stakeholder survey. Issue 8 (3rd August 2019) - Ali, Joseph; DiStefano, Michael J.; Coates McCall, Iris; Gibson, Dustin G.; Al Kibria, Gulam Muhammed; Pariyo, George W.; Labrique, Alain B.; Hyder, Adnan A.
ABSTRACT: Active public health surveillance has traditionally been carried out through face-to-face household surveys or contact with providers, which can be time and resource intensive. The increasing ubiquity of mobile phones and availability of phone survey platforms provide an opportunity to explore the use of mobile phone surveys (MPS) for active disease and risk factor surveillance, including for non-communicable diseases (NCDs). Scholars are increasingly examining the ethics implications of mobile health (mHealth), but few have focused on the ethics of mHealth in low- and middle-income countries (LMICs), and even fewer on mHealth for active surveillance. Given that little is known about ethics-related attitudes and practices of stakeholders invested in the conduct and oversight of mHealth in LMICs, we undertook a cross-sectional global stakeholder survey of ethics-related issues implicated by active observational MPS, with a contextual frame of monitoring NCD risk factors in LMICs. We analyse these findings with an organising focus on ethical issues that arise before, during and after conduct of an MPS including defining the activity; anticipating harms and benefits; obtaining consent; data ownership, access, and use; and ensuring sustainability. Finally, we present a set of empirical, conceptual, and normative considerations that arise from this analysis and merit further consideration.